Pretreatment Neutrophil-to-Lymphocyte Ratio (NLR) May Predict the Outcomes of Advanced Non-small-cell Lung Cancer (NSCLC) Patients Treated With Immune Checkpoint Inhibitors (ICIs) - Li, Ye; Zhang, Zhibo; Hu, Yi; Yan, Xiang; Song, Qi; Wang, Guoqiang; Chen, Runzhe; Jiao, Shunchang; Wang, Jinliang (Frontiers in Oncology, 2020)
Background: Recent studies have demonstrated the predictive value of pretreatment neutrophil-to-lymphocyte ratio (NLR) in advanced cancers; however, the role of NLR in patients with advanced non-small-cell lung cancer (NSCLC) treated with immune checkpoint inhibitors (ICIs) remained to be explored. Thus, we aimed to investigate whether pretreatment NLR was associated with the outcomes of advanced NSCLC patients treated with ICIs. Methods: A comprehensive literature research was first conducted in PubMed, the Cochrane Central Library, and Embase for studies that evaluated the association between pretreatment NLR and survival of advanced NSCLC patients with ICIs treatment. We then conducted a retrospective study in Chinese People's Liberation Army (PLA) General Hospital (Beijing, China) to validate these findings. Results: A total of 17 eligible studies with 2,106 patients were included in our meta-analysis, of which, 12 studies reported progression-free survival (PFS), and 13 studies reported overall survival (OS). The pooled results showed that high pretreatment NLR was significantly associated with poorer PFS (HR = 1.44, 95% CI 1.26–1.65; P < 0.001) and OS (HR = 2.86, 95% CI 2.11–3.87; P < 0.001) compared with those with low pretreatment NLR. Subgroup analysis demonstrated that the association between baseline NLR and PFS remained significant except that the cut-off value of NLR was 3 (HR = 1.48, 95% CI 0.93–2.37; P = 0.098) and region of Asia (HR = 1.55, 95% CI 1.00–2.39; P = 0.051). These results were further validated in our retrospective study that patients with pretreatment NLR ≥ 6.0 had shorter PFS (median: 5.0 vs. 9.1 months, HR = 1.39; 95% CI 1.01–1.91; P = 0.02) and OS (median: 10.0 vs. 17.3 months, HR = 1.71; 95% CI 1.18–2.46; P < 0.001) compared with those with NLR < 6.0. The associations between NLR and survival were consistent in subgroup analysis stratified by age, gender, ECOG PS, histology, stage, smoking history, treatment, and prior lines of therapy. Dynamics of NLR (dNLR) that increased ≥3.0 from baseline was also significantly associated with worse PFS (median: 3.1 vs. 9.1 months; P = 0.01) and OS (median: 6.8 vs. 17.0 months; P < 0.0001). Conclusions: Our study demonstrates that pretreatment NLR and dNLR from baseline are associated with the outcomes of advanced NSCLC patients treated with ICIs; however, it warrants further prospective studies.